The Effect of Financial Literacy, Income Level on Financial Well-Being through Financial Behavior as a Mediating Variable - Ramadhani, Salsa Diva; Norisanti, Nor; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study is entitled The Effect of Financial Literacy and Income Level on Financial Well-Being through Financial Behavior as a Mediating Variable with the research object of the Indonesian Action Figure Collector (KAFI) community. This study aims to analyze the extent to which financial literacy and income level affect financial well-being through financial behavior as an intermediate variable. The method used is quantitative with an associative design, using purposive sampling technique on 225 respondents from a total population of 18,000 KAFI members. Data were collected through observation, questionnaires, documentation, and literature study, then analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that financial literacy, income level, and financial behavior each have a significant positive effect on financial well-being. In addition, financial behavior is proven to significantly mediate the effect of financial literacy and income level on financial well-being. These findings confirm the importance of financial education not only to increase understanding, but also to encourage wise financial behavior, so that financial well-being can be achieved optimally, especially in young groups who tend to be consumptive.